Question:
What is 3(x + 2) - 2(x + 1)?
Steps:
When you solve this type of equation always use the distributive property formula to solve this equation!
Formula: a(b + c) = ab + ac
So, what is 3(x + 2) ?
Also, what is -2(x + 1)?
Then, put it back into the equation for you to solve this problem.
So, this would be the new equation:
3x + 6 - 2x - 2
Then, what you want to do is put variables next to each other and the numbers next to each other so it will be easier to simplify:
3x - 2x + 6 - 2
Then, simplify:
x + 4 is the answer!
Since 3x - 2x = x and 6 - 2 = 4
Hope that helped!!
~Serina
Answer:
y=2x+7
Step-by-step explanation:
y-y1=m(x-x1)
y-9=2(x-1)
y=2x-2+9
y=2x+7
Answer:
Step-by-step explanation:
slope m= (y2-y1) / (x2-x1) = 15-12 / 4-4 = 3/0 is undefined since we can not divide by 0
slope is undefined so the line is vertical
Number of cubes increases by 3 for each term.
an= 3n+1
20/2.5 = 8
So 8 movies can be shown in 20 hours.